INTEGRATION OF CONFIRMATION EXPECTATIONS, JUSTICE, TRUST, AND RESPONSIBILITY MODELS, PERCEPTIONS, IN EXPLAINING COMPLAINTS BEHAVIOR ON ONLINE SHOPPING SITES - Frank Aligarh (Berkala Akuntansi dan Keuangan Indonesia, 2017)
This study aims to examine the factors of fairness, expectation of confirmation, trust, perceived responsiveness in influencing customer satisfaction and its consequences in influencing the intention to make a complaint. This study develops the study of Wu (2013) which expands the confirmation expectation model in explaining complaint behavior. The constructs used are distributive justice, procedural justice, interactional justice, confirmation expectations, perceived usefulness, trustworthiness, perceived responsiveness, customer satisfaction and intention to complain.This study uses a survey method conducted to 201 respondents. This study uses the Structural Equation Model (SEM) as a statistical test tool.The results showed that apart from procedural justice and interactional justice, all constructs were positively related to customer satisfaction. The results also show that customer satisfaction is not negatively related to the intention to make a complaint. This indicates that the majority of respondents have high collectivist values which tend to have no intention to make complaints. This also confirms the research of Liu and Mclure (2001) which states that people who have collectivist values tend not to have the intention to make complaints.